False positive technetium-99m pyrophosphate scintigraphy in a patient with cardiac amyloidosis light chain: Case report. Issue 17 (30th April 2021) - Zeng, Yu; Poterucha, Timothy J.; Einstein, Andrew J.; Zhang, Qing; Chen, Yucheng; Xie, Hangyu; Wan, Ke; Liang, Yujia; Chen, Juncheng; Tang, Gongshun
Abstract: Introduction: Patients with cardiac amyloidosis light chain (AL) present with negative Tc-99m pyrophosphate (PYP) scintigraphy (absent or mild heart uptake). On the contrary, patients with cardiac amyloidosis transthyretin (ATTR) present with positive Tc-99m PYP scanning (intensive heart uptake). We present a false positive Tc-99m PYP scintigraphy (grade 2, the heart-to-contralateral ratio is 1.65) in a patient with AL. Patient concerns: A 42-year-old Chinese man complained of effort intolerance, chest discomfort, and short of breath progressively over 1 year. New York Heart Association Class III. Physical examination showed legs swelling. Laboratory revealed elevated brain natriuretic peptide of 23, 031 ng/mL (0–88) and Troponin-T of 273.4 ng/mL (0–14). Diagnosis: Cardiac amyloidosis light chain. Evidences: free light chains (FLCs): decreased serum free kappa/lambda ratio of 0.043 (0.31–1.56). Immunofixation electrophoresis: a positive lambda light chain monoclonal protein. Cardiac biopsy: HE: Ambiguity Congo red strain. Myocardial immunofluorescence: positive lambda light chain. Myocardial immunohistochemistry: positive lambda light chain, negative kappa light chain, and TTR. Interventions: Furosemide 40 mg qd, torasemide 20 mg qd, spirolactone 20 mg qd, potassium chloride 10 mL per 500 mL urine, atorvastatin calcium tablet 20 mg qd, aspirin enteric-coated tablets 100 mg qd during the 2-weeks in-hospital. Outcomes: The patient died 2 months later after discharge. Conclusion: False positive Tc-99m PYP scintigraphy may rarely presented in patients with cardiac amyloidosis light chain. So, the clonal plasma cell process based on the FLCs and immunofixation is a base to rule out AL cardiac amyloidosis when we interpret a positive Tc-99m PYP scintigraphy.